HIKMA – A TEACHING METHOD TO INSPIRE HIGHER LEARNING - Muhammad Jawad Hashim (CV. ADIBA AISHA AMIRA, 2023)
Existing teaching methods are uninspiring and diminish the desire to learn. A new teaching format, hikma, was developed to inspire learning and acquire wisdom. Hikma is a well-prepared narrative lecture followed by scholarly open discussion on a topic. It is delivered by a learned teacher to a group of students. A written guide for students outlines expectations and etiquettes for the session. Learners listen respectfully without interrupting. The teacher’s presentation is carefully prepared and well planned. The presentation includes definitions, examples, case studies, findings from research, as well as historical perspective, personal experiences, stories, and quotes. Content is selected to weave a central message. The talk progresses logically and builds an argument leading to a conclusion that the students can infer (guided discovery). Presentation style stimulates reflection and introspection. Students’ questions are kept towards the end to prevent the discourse from being side-tracked. In the second part of the session, a focused discussion is moderated by the teacher. Each student is given the opportunity ask a carefully thought-out question. After the discussion, the teacher reiterates the key learning points to close the session. In essence, hikma is a teaching format based on skilled scholarly narrative and open discourse. Hikma is designed to nurture reflection, deep thinking, and respect for wisdom.